Analisis Kasus Penggunaan Media Pembelajaran Microsoft Powerpoint Pada Mata Pelajaran IPS Di SMPN Kota Pontianak - Lestari, Febryanti Dwi; Buwono, Sri; Barella, Yusawinur; Aminuyati, Aminuyati; Wiyono, Hadi (Peneliti.net, 2024)
In Indonesia, teachers' ability to undertake research is still below average. This is due to a lack of research knowledge and experience among teachers. As a result, teachers rarely conduct research and have never published a scientific paper. This study aims to determine of teachers in the use of microsoft powerpoint learning media in social studies subjects. The research approach used is qualitative with a case study method. The data sources used are primary and secondary. Primary data includes one grade 7 social studies teacher, the Principal and the Head of Curriculum. While the secondary data used in this research are observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. From this research, the results show that there are obstacles experienced by grade 7 social studies teachers in using microsoft powerpoint learning media. The obstacles experienced are the lack of skills and creativity of teachers in using powerpoint features, lack of time, and difficulty in operating the powerpoint. However, social studies teachers also tried several ways to overcome the obstacles in using powerpoint media such as staying focused on facing problems, asking fellow teachers, learning independently through the internet, asking for help from other teachers, and adjusting the material with the duration of learning so that the implementation of learning activities in the classroom can run effectively and efficiently.